2004
DOI: 10.1590/s0100-879x2004000300011
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral modulation by mutilation pictures in women

Abstract: Previous studies have shown that women are more emotionally expressive than men. It is unclear, however, if women are also more susceptible to the emotional modulation of behavior imposed by an affective stimulus. To investigate this issue, we devised a task in which female subjects performed six sequential trials of visual target detection following the presentation of emotional (mutilation and erotic) or neutral pictures (domestic utensils and objects) and compared the data obtained in the present study with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
7
0
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
4
7
0
3
Order By: Relevance
“…In particular, the viewing of pictures of mutilated bodies is especially powerful (Azevedo et al, 2005;Bradley et al, 2003;Pereira et al, 2004). The results of the present experiments strengthen the view that the processing of emotional stimuli is prioritized, as is indicated by the interference of unpleasant pictures.…”
Section: Discussionsupporting
confidence: 83%
“…In particular, the viewing of pictures of mutilated bodies is especially powerful (Azevedo et al, 2005;Bradley et al, 2003;Pereira et al, 2004). The results of the present experiments strengthen the view that the processing of emotional stimuli is prioritized, as is indicated by the interference of unpleasant pictures.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, epidemiological studies indicate that women are at a higher risk for affective disorders, such as anxiety and depression, suggesting a higher incidence of negative affect (Sachs-Ericsson & Ciarlo, 2000). On the other hand, other studies have shown that women exhibit a pattern of behavior and physiological response similar to that observed in men when exposed to the same emotional stimuli (Kring & Gordon, 1998;Pereira et al, 2004). As suggested by Pereira and colleagues (2004), one possibility is that women and men differ only in the expression of emotion, but that the responses and influences of emotional stimulation are the same in both sexes.…”
Section: Discussionmentioning
confidence: 84%
“…When viewing pictures of 'mutilation', women, especially, show marked psychophysiological reactions [31]. Our behavioral observations demonstrated that our negatively valenced baby faces were not evaluated as emotionally ambiguous stimuli (infants in distress might elicit approach-related behavior and the image of a crying child may invoke the desire to console rather than the desire to abandon…”
mentioning
confidence: 81%
“…We calculated a mean maximum t defined as the mean of those 5% highest t-values for each left and right amygdala. The final ROIs contained the voxels in the masked maps with a t-value above 20% of the mean maximum t. This When viewing pictures of 'mutilation', women, especially, show marked psychophysiological reactions [31]. Our behavioral observations demonstrated that our negatively valenced baby faces were not evaluated as emotionally ambiguous stimuli (infants in distress might elicit approach-related behavior and the image of a crying child may invoke the desire to console rather than the desire to abandon [10]).…”
mentioning
confidence: 99%